Prove that $\frac{t^{x-1}}{1+t^y} = \sum_{n=0}^{\infty} (-1)^nt^{x-1+yn}$.

I tried expanding the exponential terms by substituting the definition of exp such that I have a series in the numerator and denominator but no matter how I tried manipulating the expressions, I wasn't able to show the equality.

Thanks in advance, whiterock.

up vote 1 down vote accepted

$$\sum_{n=0}^{\infty} (-1)^nt^{x-1+yn} = \sum_{n=0}^{\infty} (-1)^nt^{x-1}(t^y)^n = t^{x-1}\sum_{n=0}^\infty(-t^y)^n = t^{x-1} \frac{1}{1-(-t^y)}=\frac{t^{x-1}}{1+t^y}$$ whenever the exponentials are well defined and $|t^y|<1$.

  • 1
    Thank you! Wouldn't have thought that in this direction it's so much easier than the other. One minor thing: you forget the "- 1" in the exponent right at the end :) – whiterock Nov 8 at 20:46
  • Thank's and you're welcome. – Tito Eliatron Nov 8 at 20:51

Your Answer

 

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.